OPTIMASI RASIO CAMPURAN BIOETHANOL-ACETON-RON 95 TERHADAP DAYA DAN EMISI GAS BUANG PADA MOTOR 125 CC: STUDY OF OPTIMIZATION RATIO OF BIOETHANOL-ACETON-RON 95 MIXTURE FOR 125 CC MOTOR POWER AND EMISSIONS - Frandis Arvicky Farel; Hadi, Sugeng (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2023)
Bioethanol and Acetone are alternative fuels to fossil oil. Bioethanol and Aceton have some advantages in their use as fuels not only because of their renewable nature, these alternative fuels are also believed to reduce some motor vehicle emissions. Bioethanol and acetone have advantages over gasoline, namely a greater octane number. The purpose of this research is to determine the effect of using a combination of Bioethanol, Aceton and RON 95 on power and CO and HC emissions, and to determine the optimization of the fuel ratio on a 125 cc motorcycle by changing the fuel combination and engine speed. This study was conducted by testing on dynotest and Gas Analyzer with CO and HC measurement parameters. Tests on motorcycles were tried with Bioethanol-Acetone mixture ratio, RON 95 with a mixture ratio of 50%:50% (3:7:10; 5:5:10; 7:3:10), 75%:25% (10:5:5; 7.5:7.5:5; 5:10:5), 25%:75% (2.5:2.5:15; 3.5:1.5:15; 1.5:3.5:15). The results of this test are fuel mixture, power test results, CO and HC emission test results. With the optimal power mixture at a ratio of 50% Bio-Ace: 50% RON 95 (3:7:10) at 6000 rpm with 7.85 HP, then in the emission test results obtained the lowest CO content at a mixture ratio of 10:5:5 at the initial rotation (2000 rpm) with a CO content of 0.18% and decreased to 6000 rpm with a CO emission content of 0% and the lowest HC content at a mixture ratio of 10:5:5 at the initial rotation (2000 rpm) with 110 ppm and decreased to 6000 rpm with 0 ppm, then the optimal ratio optimization at a mixture of 50%: 50% with AFR of 13.95: 1.